Identifikasi Bahaya dan Risk Assessment: Penerapan Keselamatan dan Kesehatan Kerja di Laboratorium - Desy Indarwati (Jurnal Pengelolaan Laboratorium Pendidikan, 2020)
Risk Assessment is systematic way of carrying out activities in laboratory, identifying the potential emergence of hazards and other worst possibility, and also the decisions to control and prevent the accidents. This research is a qualitative descriptive research with a case study method.  Data obtained through observation, interview, and study documents at Laboratory of Tarbiyah Faculty UIN Sunan Ampel Surabaya. The purpose of this study is to provide an understanding for laboratory users about the importance of implementing occupational safety and health in the laboratory. The result show that there were 14 potential hazards that arose which were divided into four variables, they are handling and storage of materials, design of workshop/laboratory, Facilities, and activities in laboratory. Risk assessment result of 14 potential hazards found that, 43% are low risk, 14% are moderate risk, 43% are high risk, and 0% are extreme risk. The effort to implementing occupational health and safety (K3) have not been fully carried out optimally. To control or push down the potential of hazards are (1) Arranging SOP for implementation of K3, (2) provide Material Safety Data Sheet (MSDS), (3) maximize utilization of personal protective equipment, (4) provide enough first aid and eyewash, (5) provide fire extinguishers (APAR).